A study of clinical, bacteriological and radiological profile of severe pneumonia in children - Neelagiri Udaya Kumar * (Perspectives In Medical Research, 2020)
Pneumonia continues to pose a threat to health of children in developed and developing countries despite improvements in socioeconomic status, immunization and early diagnosis and treatment. Universality, vulnerability and frequency of occurrence of ALRTI in children are well recognized all over the world. Methods: This prospective clinical study of severe pneumonia conducted on n=150 children who were admitted to pediatric wards and PICU in PIMS, Nagunoor, Karimnagar. A detailed examination of each child including anthropometry was carried out. During the general physical examination, emphasis was laid on assessing general condition of the child, respiratory rate (counted over 1 minute), presence of fever and other signs such as cyanosis and pallor. Detailed systematic examination of the respiratory, cardiovascular and central nervous system was done. Any associated illness such as septicemia, meningitis and congestive cardiac failure if present was noted. Result: In this prospective study, n=150 cases of severe pneumonia were studied. In the present study, majority of cases (53%) were less than one year of age. majority of the cases were diagnosed as Bronchopneumonia (66.67%), Lobar pneumonia was diagnosed in 18.6% of cases and pneumonia and its complications in 9.3% of cases. In the present study, radiological findings were present in 80.66% of cases Bacterial pneumonia was detected in 62.67%, viral pneumonia in 14%. Culture was positive in only of cases. S. pneumonia was the most common organism isolated (6 cases) followed by S. aureus (n=5 cases) and Klebsiella (n=3 case). n the present study, antibiotics were given in all cases. Conclusion : In this study we found Bronchopneumonia is the predominant form of presentation in infants and preschool children. Among the risk factors studied, previous history of similar illness, inappropriate immunization for age, anemia, PEM grade 3 and 4, were found significant causes for severe pneumonia